Sektor unggulan Asahan - Nur Sakinah; Zulfa ‘Afifah; Rahel Hutahean (Jurnal UMKM, Manajemen dan Akuntansi, 2026)
This study analyzes the leading sectors in Asahan Regency using the Location Quotient (LQ) and Shift Share methods. The data used are the Gross Regional Domestic Product (GRDP) of Asahan Regency and North Sumatra Province for the period 2019-2023. The results of the analysis show that the Agriculture, Forestry, Fisheries, and Processing Industry sectors are the basic sectors in Asahan Regency, which contribute significantly to the local economy. Additionally, these sectors have the potential to enhance the region's competitiveness through the utilization of local resources and increased exports. However, several non-basic sectors still require special attention to improve their performance. An integrated strategy, including strengthening human resource capacity, applying appropriate technology, and support from local government policies, is essential to promote sustainable economic growth in Asahan Regency.